2022
DOI: 10.1186/s12936-022-04224-4
|View full text |Cite
|
Sign up to set email alerts
|

Making data map-worthy—enhancing routine malaria data to support surveillance and mapping of Plasmodium falciparum anti-malarial resistance in a pre-elimination sub-Saharan African setting: a molecular and spatiotemporal epidemiology study

Abstract: Background Independent emergence and spread of artemisinin-resistant Plasmodium falciparum malaria have recently been confirmed in Africa, with molecular markers associated with artemisinin resistance increasingly detected. Surveillance to promptly detect and effectively respond to anti-malarial resistance is generally suboptimal in Africa, especially in low transmission settings where therapeutic efficacy studies are often not feasible due to recruitment challenges. However, these communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…Further quantitative results are reported elsewhere. [12] A total of 46 healthcare workers participated in five separate FGDs, with group sizes ranging from 8 -12 participants. Of the participants, 32 were nurses (including professional nurses, occupational nurses, and assistant nurses), and 14 were environmental health officers who worked as health promoters or malaria case investigators, data clerks, data capturers and surveillance officers.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further quantitative results are reported elsewhere. [12] A total of 46 healthcare workers participated in five separate FGDs, with group sizes ranging from 8 -12 participants. Of the participants, 32 were nurses (including professional nurses, occupational nurses, and assistant nurses), and 14 were environmental health officers who worked as health promoters or malaria case investigators, data clerks, data capturers and surveillance officers.…”
Section: Resultsmentioning
confidence: 99%
“…Previous evidence has shown that integrating antimalarial molecular markers using a routine malaria notification system is feasible in sub-Saharan African settings. [12] However, little is known about the barriers and enhancers to integrating molecular markers of resistance within the routine malaria surveillance system.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 3 more Smart Citations